Eksplorasi Nilai Budaya Melukat Dalam Pariwisata Berkelanjutkan, Perspektif Komunikasi - Gabriella, Fenika; Rasyidin, Nikita; Roxanne, Roxanne; Parani, Rizaldi (CV. ITTC INDONESIA, 2023)
Tourism is an important industry in many countries, often based on cultural attractions and traditions. In an effort to maintain sustainable tourism while preserving cultural heritage, exploring the cultural values of Melukat in Bali shows the importance of a communication perspective. This research explores the cultural value of Melukat in sustainable tourism with a focus on communication. This research argues that to preserve cultural heritage and promote sustainable tourism, effective communication is needed in several aspects. This includes a thorough understanding of local culture, respect for traditions, tourism education and environmental awareness campaigns. Apart from that, media also plays a role in combining cultural values with the creation of interesting and useful tourism experiences, so that it can have an impact on the economic development of local communities. The research results show that communication is an important factor in maintaining and promoting Melukat's cultural values while supporting sustainable tourism. Furthermore, this research also addresses the challenge of maintaining a balance between commercialization and cultural preservation in the tourism context.